Influence of swift heavy ions on aluminum thin films. (2022) - Aftab, Zara; Sulania, Indra; Kandasami, Asokan; Nair, Lekha
Abstract: Controlled ion beam irradiation of the target material results in material modification as the ions give away their energy to the material, either by interacting with electrons, a process designated as electronic energy loss (Se ) or by interacting with the nuclei, known as nuclear energy loss (Sn ). As a consequence, changes occur in the structural and electronic properties of the material that need to be systematically investigated. In this work, 25 nm thin Aluminium films were deposited over a silicon substrate and subjected to 100 MeV O 7+ and 100 MeV Si 7+ ion irradiation with ion fluences varying from 1 × 10 11 to 1 × 10 13 ions/cm 2 . The swift heavy ion (SHI) irradiated and pristine films are then characterised using Glancing Incident X-Ray Diffraction (GIXRD), Rutherford Backscattering Spectrometry (RBS), Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM), to study the effects of the irradiation with different ion species, having a large variation in Se and Sn . The GIXRD analysis revealed the change in crystallinity along with the change in crystallite size as compared to the pristine film. RBS studies indicate no change in the composition as there is negligible evidence of electronic sputtering. AFM shows that the irradiation of the film results in restructuring, with the particle size distribution shifting towards a lower value, while the surface roughness reduces from 2.8 ± 0.24 nm for the pristine surface to 1.35 ± 0.03 nm for O 7+ and 1.63 ± 0.27 nm for Si 7+ ion irradiated surfaces at the fluence of 1 × 10 13 ions/cm 2 . SEM results confirm grain fragmentation as the irradiation proceeds, and also reveal the decrease in roughness values.